2013
DOI: 10.1007/s00223-013-9822-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Weight Status on Radial Bone Mineral Density in Lebanese Women

Abstract: The aim of this study was to investigate the influence of the weight-status (obese, overweight and normal-weight) on bone mineral density of the forearm in Lebanese women. 3,989 Lebanese women (1,138 obese, 1,570 overweight and 1,281 normal weight) aged from 19 to 92 years old participated in this study. Weight and height were measured, and body mass index (BMI) was calculated. BMD of the ultra-distal (UD) radius, the 1/3 radius and the total radius was measured by DXA (GE Healthcare Lunar Prodigy). In the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…In our study, BMI, height, weight were positively correlated with BMD indicating their protective role for bones which is in line with widely reported literature [ 22 , [41] , [42] , [43] ]. Wu and Du [ 43 ] discussed that the basic correlation mechanisms are multidimensional, including mechanical load, hormones, and nutritional status.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, BMI, height, weight were positively correlated with BMD indicating their protective role for bones which is in line with widely reported literature [ 22 , [41] , [42] , [43] ]. Wu and Du [ 43 ] discussed that the basic correlation mechanisms are multidimensional, including mechanical load, hormones, and nutritional status.…”
Section: Discussionsupporting
confidence: 93%
“…[ 30 ] However, the results were inconsistent with the results of the study conducted by El Hage et al who reported obesity is associated with higher levels of BMD. [ 22 ] In the present study, BMI was not associated with higher BMD of the radius. Based on the regression analysis, it was shown that BMD values in women in the lumbar, total femoral, and radius areas were significantly lower than those in men.…”
Section: Discussioncontrasting
confidence: 49%
“…In the present study, regression analysis revealed that per 1 year increase in age, BMD decreases by −0.477 in the lumbar area, −0.238 in the total femoral area, −0.002 in the femoral neck area, and −0.417 g/cm 2 in the radius area, which all of them were statistically significant, confirming some of the previous studies, including the study conducted by Alonso et al in Brazil[ 21 ] and El Hage et al in Lebanon. [ 22 ] Moreover, the results of this study showed that per one unit of increase in BMI, BMD in the lumbar area increased by 0.01 g/cm 2 on average, BMI values >30 did not result in a drop in BMI in the lumbar area and the values increased linearly. In addition, per one unit of increase in BMI, BMD in the total femoral area and femoral neck increased by 0.258 and 0.007 (g/cm 2 ), respectively, which was significant.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The TBS score can assist the healthcare professional in assessing fracture risk (20,21). In our laboratory, the coefficients of variation were less than 1% for BMC and BMD and less than 3% for FN CSA (22)(23)(24)(25). The same certified technician performed all analyses using the same technique for all measurements.…”
Section: Bone Variablesmentioning
confidence: 94%